Iron(II) djenkolate: synthesis and properties - Melnikov, P.; Corbi, P. P.; Aguila, C. D.; Zacharias, M. A.; Cavicchioli, M.; Massabni, Antonio Carlos [UNESP] (Elsevier B.V., 2000)
Djenkolate complex of iron, [Fe(C(7)H(12)N(2)O(4)S(2))]. H(2)O, has been synthesized by the reaction of potassium djenkolate with Fe(SO(4)). 7H(2)O under nitrogen atmosphere. X-Ray diffraction pattern has been indexed in orthorhombic system with lattice parameters: a=11.24 Angstrom, b=7.50 Angstrom and c=6.96 Angstrom. According to IR spectroscopy, coordination is performed through COO(-) and NH(2) groups. An octahedral geometry for Fe ion is suggested by UV-Vis and Mossbauer spectroscopies. Thermal decomposition leads to the formation of Fe(2)O(3) (hematite). The compound shows poor solubility in water and in common organic solvents. (C) 2000 Elsevier B.V. S.A. All rights reserved.
Keywords: x-ray diffraction